Holistic Orientation in Education: Transformative Art of Including, Connecting and Balancing - Ojha, Gaurav (Journal of Transformative Praxis, 2020)
This study explores holistic orientation in education reflecting on practice-based accounts of educators with emerging pedagogical insights and implication conceptualized within transformative learning theory. Similarly, this study explores holistic orientation in education with a reflective praxis that advances collaborative self-narrative research incorporating personal reflections of educators seeking to nurture transformed ways of including, connecting and balancing in their pedagogical practices. In this study, educators with holistic orientations place emphasis on inner lives, balance, exploring dynamics of interconnections, trustful and authentic relationships, dialogues, concern and care as transformative initiatives in their pedagogical practices. Based on the guiding metaphor that what you see depends upon how you look, this article offers both descriptive and reflective insights into pedagogical reflections of educators that exemplify holistic orientations as a practical implication for transformative learning. The findings of this article indicate holistic orientations in education as a resonance educators experience and explore between why they teach and how they teach. More importantly, together with further implications for transformative research and education policy, this study aims to recreate possibilities for transforming educational practices with transformed ways of being, balancing, and relating of educators.